Analisis Budaya Dan Kelas Sosial Terhadap Keputusan Pembelian Pada Teanol Cabang Telanaipura Kota Jambi - Mappadeceng, Riko; Tarmizi, Ahmad; Putri Liantoni, Sonia Rosa (Universitas Batanghari Jambi, 2023)
This study aims to determine the description of culture, social class and purchasing decisions at Teanol Telanaipura Branch, Jambi City and to determine the simultaneous and partial influence of culture and social class on purchasing decisions at Teanol, Telanaipura Branch, Jambi City. The research method used in this research is descriptive and quantitative research. Primary data is specifically collected by researchers to answer research questions collected using questionnaires. The analytical tool used is multiple linear regression. Based on the research results it is known or obtained that the F count is 83.184 greater than the F table which is 3.09 or the F-sig significance of 0.000 is less than 0.05 which indicates that cultural class and social class jointly (simultaneously) have a significant effect on decisions purchases at Teanol Telanaipura Branch, Jambi City. Based on the results of the study, it was found that the t count was 3.050, which was greater than the t table, which was 1.660. Then the probability value for the culture class variable is 0.000. with a confidence level (Î± = 5%), from these calculations it can be seen that the probability value is smaller than alpha (0.003 <0.05) meaning that cultural class has a significant positive effect on purchasing decisions at Teanol Telanaipura Branch, Jambi City. Furthermore, it is obtained that t count is 6.335 which is greater than t table which is 1.660. Then the probability value for the social class variable is 0.000. with a confidence level (Î± = 5%), from these calculations it can be seen that the probability value is greater than alpha (0.000 <0.05, meaning that social class has a significant effect on purchasing decisions at Teanol Telanaipura Branch, Jambi City.